2018
DOI: 10.1002/pen.24927
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical, Thermal, Rheological and Morphological Properties of PLA/PBAT Blown Films by Using Bis(tert‐butyl dioxy isopropyl) Benzene as Crosslinking Agent

Abstract: Blown films of poly(lactic acid) (PLA)/poly(butylene adipate‐co‐terephthalate) (PBAT) blends were prepared, bis(tert‐butyl dioxy isopropyl) benzene (BIBP) as crosslinking agent. From wide‐angle X‐ray diffraction results, PLA/PBAT/BIBP involved all the diffraction peaks were consistent with PLA and PBAT. For the DSC curves of PLA/PBAT/BIBP films, there were two glass transition temperature and two melt temperature, there existed two step decomposition in the thermogravimetric curves. Both Han plots and Cole–Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…The first type of chart presenting the imaginary viscosity (η" = G"/ω) versus real viscosity (η' = G'/ω) values displays semicircular-shaped curves of unmodified POM/PLA blends. This type of behavior confirms the good compatibility between blend phases, which also confirms the miscibility of these polymers in the molten state [59,60]. However, for EBA/CE-modified blends the Cole-Cole plots show a large deviation from the semicircular smooth shape.…”
Section: Rheological Measurementssupporting
confidence: 71%
“…The first type of chart presenting the imaginary viscosity (η" = G"/ω) versus real viscosity (η' = G'/ω) values displays semicircular-shaped curves of unmodified POM/PLA blends. This type of behavior confirms the good compatibility between blend phases, which also confirms the miscibility of these polymers in the molten state [59,60]. However, for EBA/CE-modified blends the Cole-Cole plots show a large deviation from the semicircular smooth shape.…”
Section: Rheological Measurementssupporting
confidence: 71%
“…Among the first class of reagents, the use of peroxides grants the possibility to generate inter-macromolecular covalent bonds between PLA e PBAT, producing a PLA-PBAT copolymer, which acts as a compatibilizer at the interface [ 93 , 94 , 95 , 96 ]. Coltelli et al, studied the reactivity of PLA, PBAT and PLA/PBAT 75/25 towards 2,5-dimethy-2,5-di(tert-butylperoxy) hexane [ 93 ] by evidencing the nonselective strategy of this approach.…”
Section: Pla/pbat and Pla/pbsa Blends: Preparation And Characterizationmentioning
confidence: 99%
“…More recently the properties of PLA/PBAT blend films treated with 0.1 wt% of bis(tert-butyl dioxy isopropyl) benzene (BIBP) were analyzed by changing the polymers ratio [ 96 ]. For this study, a PBAT copolymer with a slightly different composition was used: 45% BA- co -55% BT.…”
Section: Pla/pbat and Pla/pbsa Blends: Preparation And Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] PLA has been blended with poly(ε-caprolactone) (PCL), [9][10][11][12][13] poly((butylene succinate)-co-adipate), [14][15][16][17] poly(butylene succinate), [18][19][20][21] and poly(butylene adipate-co-terephthalate) (PBAT). [17,[22][23][24][25][26][27][28][29] Although blending has been found to be an effective way to enhance the ductility and thermal properties of PLA, the immiscibility of the blend could cause the formation of phaseseparated morphologies depending on the blend ratio, molecular weight, interfacial tensions, and processing conditions. [22,[30][31][32] It has been shown that different morphologies, and thus different properties, can be obtained if these parameters are varied.…”
Section: Introductionmentioning
confidence: 99%